Physical Properties of Bio-oils used as cutting fluids during drilling operation of Mild steel - M, Susmitha; P.N, Jyothi.; Mopathi, Bharath Kumar (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
Cutting fluids are used during machining process to reduce heat and friction on both tool and work piece. The cutting fluids produce three positive effects in the process i.e. heat removal, lubrication on the chiptool interface and chip removal. Normally used petroleum based cutting fluids damage soil and water resources, causing serious environmental impacts even machine operators are affected by the negative effects of cutting fluids, such as skin and respiratory problems. For these cases alternative solutions are developed to avoid environment and health. The use of vegetable oils allows high performance in machining combined with good environment compatibility could be achieved. Compared to mineral oil, vegetable oil can even enhance the cutting performance, extend tool life and improve the surface finish. As vegetable oils are not toxic to the environment, biodegradable if spilled and have high flash and fire points. The present paper discusses the measurement of physical properties of Neem, Karanjaand blend of these two oils (50%Neem-50%Karanja, 33.3% Neem 66.6% Karanja, 66.6% Neem-33.3% Karanja) and results are compared with petroleum based SAE 20W40.